1998
DOI: 10.1016/s0006-8993(98)00584-8
|View full text |Cite
|
Sign up to set email alerts
|

Central infusion of glucagon-like peptide-1-(7–36) amide (GLP-1) receptor antagonist attenuates lithium chloride-induced c-Fos induction in rat brainstem

Abstract: Central infusion of glucagon-like peptide-1-(7-36) amide (GLP-1) and intraperitoneal (i.p.) injection of lithium chloride (LiCl) produce similar patterns of c-Fos induction in the rat brain. These similarities led us to assess the hypothesis that neuronal activity caused by i.p. injection of LiCl involves activation of central GLP-1 pathways. We therefore determined if third-ventricular (i3vt) infusion of a GLP-1 receptor antagonist would block LiCl-induced c-Fos expression in the brainstem. Relative to rats p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
54
2
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 22 publications
4
54
2
1
Order By: Relevance
“…Our results also provide a potential molecular mechanism for the similar effect of lithium and GLP-1 to suppress food and water intake (3,4,(63)(64)(65)(66)(67)(68)(69)(70). Scientists have observed for a number of years that peripheral administration of lithium in rats causes a spectrum of effects, including reduced food/water intake, decreased salt ingestion after sodium depletion, and induced robust conditioned taste aversions (63)(64)(65)(66)(67)(68)(69).…”
Section: Discussionmentioning
confidence: 69%
“…Our results also provide a potential molecular mechanism for the similar effect of lithium and GLP-1 to suppress food and water intake (3,4,(63)(64)(65)(66)(67)(68)(69)(70). Scientists have observed for a number of years that peripheral administration of lithium in rats causes a spectrum of effects, including reduced food/water intake, decreased salt ingestion after sodium depletion, and induced robust conditioned taste aversions (63)(64)(65)(66)(67)(68)(69).…”
Section: Discussionmentioning
confidence: 69%
“…Future studies will be required to determine which Wnt molecule(s) regulates glu gene expression in the gut endocrine cells and whether glu expression in the brain is also regulated by lithium and the Wnt pathway. Peripheral administration of lithium was found to reduce food/water intake, decrease salt ingestion after sodium depletion, and induce robust conditioned taste aversion in rats (42)(43)(44)(45)(46)(47)(48)(49). These effects can be mimicked by central (intracerebroventricular) administration of GLP-1 (14).…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, pretreatment with the GLP-1 receptor antagonist also attenuated LiCl-induced c-FLI in the AP, NTS, and PBN. 62 We later found that the GLP-1 antagonist did not influence cholecystokinin octapeptide (CCK-8) induced c-FLI, indicating that the compound does not block c-FLI indiscriminately (unpublished data), nor did this antagonist block i3vt CCK-8's ability to produce a short-term reduction in food intake. These data indicate that central blockade of the GLP-1 receptor attenuates LiCl-induced cFLI, and suggest that neuronal activity in the brainstem caused by LiCl administration is mediated, at least in part, by GLP-1 signaling.…”
Section: Involvement Of Glp-1 Signaling In Licl-induced Neuronal Actimentioning
confidence: 98%
“…) may be involved with neuronal signaling in the brainstem following injection of LiCl. 62 A hint of such a mechanism has been provided by Rinaman,63 who observed that peripheral administration of toxins, including LiCl, stimulated c-FLI in neuronal cell bodies in the NTS that contain GLP-1. Combined tracer injections indicated that a portion of these project to the PVN.…”
Section: Involvement Of Glp-1 Signaling In Licl-induced Neuronal Actimentioning
confidence: 99%